2009
DOI: 10.1111/j.1349-7006.2009.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and involvement of special AT‐rich sequence binding protein 1 in multidrug resistance in human breast carcinoma cells

Abstract: Special AT-rich sequence binding protein (SATB) 1 has been proposed to act as a determinant for the acquisition of metastatic activity by controlling expression of a specific set of genes that promote metastatic activity. Here we found that SATB1 expression is upregulated in multidrug-resistant breast cancer cells that exhibit higher invasive potential than the parental cells. Apart from accelerating metastasis and inducing epithelial-mesenchymal transition, SATB1 was demonstrated to confer resistance to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…Notably, VCR-induced apoptosis was largely eliminated by SATB1 overexpression in SGC7901 cells. These results are consistent with previous studies which revealed that SATB1 inhibited apoptosis in Sézary and breast cancer cells (14,23), suggesting that the SATB1-mediated inhibition of apoptosis may contribute to MDR in gastric cancer.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, VCR-induced apoptosis was largely eliminated by SATB1 overexpression in SGC7901 cells. These results are consistent with previous studies which revealed that SATB1 inhibited apoptosis in Sézary and breast cancer cells (14,23), suggesting that the SATB1-mediated inhibition of apoptosis may contribute to MDR in gastric cancer.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, previous studies have suggested that SATB1 is a master regulator of breast cancer growth and metastasis (1,13). Notably, Li et al recently reported that SATB1 was able to upregulate certain genes associated with MDR and suppress drug-induced apoptosis in breast cancer, indicating the role of SATB1 in MDR (14).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the multidrug-resistant phenotype was reversed when the level of SATB1 was reduced. Previous studies suggested that SATB1 mediates the resistance of tumor cells by inhibiting tumor cell apoptosis (Li et al, 2010). Another study found that chemotherapy can reduce the level of microRNA-448.…”
Section: Discussionmentioning
confidence: 99%
“…been associated with varied malignancies [14][15][16][17] ; however, its status in CTCLs other than Sézary syndrome is unknown.…”
Section: Primary Cutaneous Cd30mentioning
confidence: 99%